DIGITAL CURRENCY REVOLUTION - Tachscherer, Balázs; Benedek, Andrea (Acta Carolus Robertus, 2021)
Background. Bitcoin protocol was released in 2009, which created a revolutionary virtual currency, the Bitcoin. Many cryptocurrencies have appeared in the last decade, and as a result nowadays approximately 4940 cryptocurrencies are registered, and new ones emerge almost every day. Majority of the central banks do not accept these cryptocurrencies as real currencies, rather they draw attention for their dangers and risks. At the same time, despite warnings, the number of cryptocurrency transactions has exploded. Research aims. The aim of this research is to examine the investors’ investing habits, motivations and study the acceptance of innovation. Our aims are to explore those habits and motivations, which are obstruct or incite investors’ investing habits. Also, one of our aims is to study how cryptocurrency investors open for innovations and which adaption categories they can be classified into. Methodology. During the research process, the professional bibliography of the academic basis for cryptocurrencies had been reviewed. We used the results of previous research in our study whilst we examined the investing, savings habits and motivations of the Hungarian population. Everett Rogers’ theory of innovation played a vital role in our research, mostly that is what our own research was based on. During the primary research we conducted a questionnaire survey, which results were analyzed using mathematical-statistical models. Key findings. The main motivation for cryptocurrency investors is gaining income, wealth and seeking entertainment. Their characteristics are mostly the independence and lifecycle motivation. For cryptocurrency investors, the motivation is mostly obstructed by lack of income and market information. Most of them are open for innovation and bear it inevitable. The most of them considered as innovator or late majority. They are rarely known as laggards.